ENGLISH LANGUAGE - IMPROVE LISTENING SKILLS: Bachelor of Science in Business Administration - Garry Alfonsius (Universal Journal, 2021)
Today English has been used as an international language so all of people in the world need to learn to speak English. But not only we learn to speak in English, we need to learn to listen, write, and read in English. On previous section I was told you how to improve English from speaking. Today I want to tell you how to improve English from listening.